SIC-Coding Schemes for Underlay Two-Way Relaying Cognitive Networks. (24th August 2020) - Son, Pham Ngoc; Duy, Tran Trung; Ho-Van, Khuong
Abstract : In this paper, we propose an underlay two-way relaying scheme with the successive interference cancellation (SIC) solution in which two secondary sources transmit simultaneously their data to each other through secondary relays. The proposed scheme is operated in only two time slots and under an interference constraint of a primary receiver, denoted as the UTW-2TS scheme. In the UTW-2TS scheme, the secondary relays employ the SIC operation to decode successively the data from received broadcast signals and then encode these data by two techniques: digital network coding (DNC) enforced by XOR operations (denoted as the UTW-2TS-DNC protocol) and superposition coding (SC) enforced by power domain additions (denoted as the UTW-2TS-SC protocol). A selected secondary relay which subjects to maximize decoding capacities and to minimize collection time of channel state information in two protocols UTW-2TS-DNC and UTW-2TS-SC experiences residual interferences from imperfect SIC operations. Outage probabilities and throughputs are solved in terms of exact closed-form expressions to evaluate the system performance of the proposed protocols. Simulation and analysis results provide performance enhancement of the proposed protocols UTW-2TS-DNC and UTW-2TS-SC owing to increase the number of the cooperative secondary relays, the interference constraints, and the distances from the secondary network to the primary receiver. The best throughputs are pointed at optimal interference power allocation coefficients and optimal locations of the selected secondary relay. Considering the same power consumption, the UTW-2TS-DNC protocol outperforms the UTW-2TS-SC protocol. Finally, the simulation results are collected to confirm the exact analysis values of the outage probabilities and throughputs.